KONSEP ETIKA BISNIS ISLAM TERHADAP JUAL BELI ONLINE DALAM PERSPEKTIF FIQIH DAN FATWA DSN-MUI NO.05/DSN-MUI/IV/2000 YANG DITERAPKAN PADA PT HIJUP.COM. - Mitra Sami Gultom; Melda Putri; Fatma Yeni (Universitas Muhammadiyah Prof Dr Hamka, 2019)
The technological developments have affected the development of online business or e-commerce. It can facilitate consumers in business transaction activities. The lack of application of Islamic Business Ethic gave the rise to cyber crime. The application of Islamic business ethics were first applied by the Messenger of Allah, who behaved fairly, honestly and reliably in carrying out his business activities.The method of this research conducted by qualitative approach which conceptualizes Islamic business ethic against online buying and selling in the perspective of Fiqih and DSN-MUI Fatwa No. 05 / DSN-MUI / IV / 2000. In conceptualizing, the researcher uses descriptive analysis in analyzing PT. Hijup.com. Based on the descriptive analysis in managing Islamic business ethics on online transaction, it shows that Islamic business ethics towards online transactions are in accordance with Fiqih and DSN-MUI Fatwa No. 05 / DSN-MUI / IV / 2000 that have been applied to PT Hijup.com. Conformity is applied because of the Hijup has developed human resource and business partners well, and the presence of new innovations in the conducting service that is in accordance with the application of Islamic business ethics. Keywords: Islamic Business Ethics, Online Transaction, Fiqh and DSN-MUI Fatwa NO. 05 / DSN-MUI / IV / 2000, PT hijup.com